2012
DOI: 10.1063/1.3686314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of work hardening on dynamic friction

Abstract: We have studied dynamic friction by impacting a copper plate onto a target consisting of a tapered, annealed, aluminium alloy plug mounted into a matching hole in a stainless steel outer sheath. The velocity of the back surface of the plug was measured using velocity interferometry. Unfortunately it was found that apparently identical configurations gave significantly different velocity profiles. Therefore a series of experiments were conducted in which the manufacturing tolerances were tightened and the assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It has been suggested that this dynamic behaviour is due to thermal softening processes occurring in the interfacial region due to the high temperatures generated, in excess of 350 K from our models. Recent analysis of final state deformation at aluminium -stainless steel sliding interfaces has suggested the formation of regions of deep and shallow deformation alongside each other, of millimetre and micrometre order respectively [7]. The presence of regions of highly elongated shallow deformation can likely be attributed to thermal softening, allowing sub-surface sliding to occur in the aluminium in addition to any relative motion at the material interface.…”
Section: Lower Sliding Velocitiesmentioning
confidence: 99%
“…It has been suggested that this dynamic behaviour is due to thermal softening processes occurring in the interfacial region due to the high temperatures generated, in excess of 350 K from our models. Recent analysis of final state deformation at aluminium -stainless steel sliding interfaces has suggested the formation of regions of deep and shallow deformation alongside each other, of millimetre and micrometre order respectively [7]. The presence of regions of highly elongated shallow deformation can likely be attributed to thermal softening, allowing sub-surface sliding to occur in the aluminium in addition to any relative motion at the material interface.…”
Section: Lower Sliding Velocitiesmentioning
confidence: 99%